Learning Strategy To Achieve High Score In Toeic Used By Students Of Muhammadiyah University Surakarta In 2013/ 2014 Academic Year - Firdaus, Erma Nurhayati; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Anam Sutopo, M.Hum (2014)
This research focuses in three points; they are first, types of learning strategies applied by Muhammadiyah students to achieve high score of TOEIC, Second, Dominant learning strategies, and the third,the reason of why the students applied such learning strategies. Therefore, The objectives of this research are (1) to find out the types of learning strategies applied by MuhammadiyahUniversity students to achieve high score of TOEIC, (2) to know the dominant learning strategies, and(3) to describe their reason to use there to use those strategies.This research is a descriptive qualitative research with a case study. The sampling technique used in this research is a total sampling techniques which analyze the types of learning strategies used by three students of Economy Faculty of Muhammadiyah University. This research applied two kinds of method of data collections: content analysis and interview by using open ended interview and questionnaire as the instrument of data analysis. The data were collected from the three students of Economy Faculty. The data were collected from the interview result and questionnaire. The data collected areanalyzed based on O'Malley taxonomy of learning strategy. The finding of the research shows that the three respondents have applied multiple strategies associated with O'Malley taxonomy of learning strategy. They are meta-cognitive, cognitive, and socio-affective. They use each type of strategy to increase their capability of learning L2 language (English). There is no significant dominant learning strategy used by them, but they have some similarity and differences of applying some strategy for listening comprehension part of TOEIC test.The three strategies of O'Malley called as meta-cognitive, cognitive, and socioaffective and its description haspower in influencing the quality of the respondent's result test. The different strategy chosen by the respondent had given different score for their TOEIC test. It proves that the type of strategy of meta-cognitive, cognitive, and socio-affective has significant impact in the quality of learning L2.